Audit Kas dan Setara Kas: Analisis Cash Opname dan Confirmation Control terhadap Asersi Penyajian dan Pengungkapan - Nabilah Izza Nuraini; Astrini Aning Widoretno (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to analyze the implementation of cash opname and confirmation control procedures in testing the assertion of presentation and disclosure of cash and cash equivalents at PT XYZ. Assertion of presentation and disclosure is an important aspect in the audit process because it is directly related to the clarity, completeness, and reliability of information in the financial statements. The research method used is qualitative descriptive, which is a method that aims to describe and explain phenomena based on actual data in the field. Data collection techniques are documentation and observation of audit activities carried out by auditors from KAP X. The results of the study indicate that the audit procedures have been carried out in accordance with applicable standards. In cash opname, although physical data was not obtained in full, the auditor still carried out procedures to assess the adequacy of presentation and disclosure of cash balances. Meanwhile, in confirmation control, no difference was found between the recorded cash balance in the bank and the confirmation results from the bank. These results indicate that both audit procedures are able to support evidence of assertions of presentation and disclosure of cash and cash equivalents reliably. The implications of this study indicate the importance of implementing appropriate audit procedures as a response to the risk of misstatement in the presentation of financial statements.